Research on the integration level measurement and optimization path of industrial chain, innovation chain and service chain - Hu Xuhua; Linyu Zhang (Journal of Innovation & Knowledge (JIK), 2023)
The contemporary scientific and technological revolution and industrial transformation are accelerating an overall industrial evolution. The integration of industrial, innovation, and service chains (three-chain) has become an important measure for countries around the world for assessing and enhancing international competitiveness. Based on regional economic theory, industrial policy theory, and synergy theory, this study constructs an evaluation index to measure three-chain integration. A model to measure the degree of synergy among the three chains of the composite system is applied using sample data from Zhenjiang, China from 2012 to 2020. The relevant results are threefold. (1) The three chains of Zhenjiang are at a low level of synergy, which exhibits a downward trend. (2) The industrial chain's degree of synergy is the lowest, and must assume more responsibility for addressing the low three-chain integration level. (3) When examining the integration of any two chains, the integration level of the industrial and innovation chains is the highest. Finally, combined with the research results, optimization paths are proposed to promote three-chain integration. This research contributes to the field by integrating industrial, innovation, and service chains into a comprehensive research framework, constructing a universally applicable evaluation index system to empirically test the level of three-chain integration, and proposing optimal paths to provide scientific methods and decision-making reference to advance three-chain research.
Keywords: O14; O32; L00; C87; C51; L80; 650; Composite system synergy degree model; Industrial chain; Innovation chain; Service chain; Three-chain integration